Exploring the causal pathway from bilirubin to CVD and diabetes in the UK biobank cohort study: Observational findings and Mendelian randomization studies. (March 2021) - Hou, Lei; Li, Hongkai; Si, Shucheng; Yu, Yuanyuan; Sun, Xiaoru; Liu, Xinhui; Yan, Ran; Yu, Yifan; Wang, Chuan; Yang, Fan; Wang, Qing; Xue, Fuzhong
Abstract: Background and aims: Some studies reported that mildly elevated serum bilirubin levels were associated with decreased risk of cardiovascular disease (CVD) and diabetes. Whether these are causal relationships remains unclear. This study aims to examine the causal effects of bilirubin on CVD, diabetes and their subtypes. Methods: The data we used in this study includes individual data from the UK Biobank cohort with 331, 002 white British participants, and summary data from published genome wide associations studies (GWAS) findings. We used individual data to perform logistic regression for the observational study and two-stage least squares method for the Mendelian randomization (MR) study. We also performed several traditional MR methods and MR-TRYX by summary data. Results: The observational study supported the association relationships between bilirubin and CVD and diabetes and their subtypes. Results of MR showed strong evidence for negative causal associations of loge total bilirubin with CVD [OR 0.92, 95%CI 0.88–0.95, p -value 2.15 × 10 −6 ], coronary heart disease [OR 0.90, 95%CI 0.85–0.96, p -value 1.54 × 10 −3 ] and hypertensive diseases [OR 0.91, 95%CI 0.88–0.95, p -value 5.89 × 10 −6 ], but no evidence for diabetes [OR 0.94, 95%CI 0.86–1.02, p -value 0.14] and its subtypes. We also obtained similar results for direct bilirubin. We found that blood pressure, cholesterol, C-reactive protein, alcohol and white blood cell count played important roles in the causal pathway from bilirubin to CVD. Two sample MR and sensitivity analyses showed consistent results with one sample MR. Conclusions: Genetically determined bilirubin was negatively associated with the risk of CVD but had no evident causal association with diabetes in the UK Biobank cohort of white British. Highlights: Genetic determined bilirubin is negatively associated with the risk of cardiovascular disease (CVD). Bilirubin has no evident causal association with diabetes in white British. We identified the mediators of the causal pathway from bilirubin to CVD.